Playing Method Application in Improving Students’ Competence of Volleyball Under-Passing Technique - Rajidin Rajidin; Awang Roni Efendi; Henry Maksum (AL-ISHLAH: Jurnal Pendidikan, 2022)
The issue in this study is the low student learning outcomes, particularly in the method of underpassing volleyball. According to the findings of the researchers' observations, the poor motivation of students when participating in learning has an effect on their below-average KKM completeness score. This study used classroom action research, which consists of two cycles with four stages of action: planning, implementing, observing, and reflecting. 32 students from only one class participated in this study. This study's data collection instrument consisted of teacher and student observation sheets as well as a grid-based assessment instrument for the movement process containing beginning attitude stages, implementation attitudes, and final attitudes. Using the playing approach, students' volleyball under-passing skills improve, with pre-cycle mastery only reaching 25%, cycle I increasing to 63%, and cycle 2 increasing to 78%. Thus, it can be stated that a Ketapang senior high school's volleyball under-passing talents can be enhanced by employing the playing approach.